INSTITUTIONALIZATION AND EMOTIONAL LABOUR BEHAVIOUR: A RESEARCH IN HOSPITALITY ORGANIZATIONS - Emine Vasfiye Korkmaz; Ali Şükrü Çetinkaya (Sosyal Ekonomik Araştırmalar Dergisi)
ABSTRACTIncreasing   competition and globalization  make  obligatory businesses to  go toward differentiation. In competitive environment, that  businesses institutionalize and  make  efforts of the  different  product and service  toward   customers enables them to proceed  one  step further  than  their competitors. It  is considered that  expecting  the behavior of  emotional labor, defined  as   emotional expression exhibited together with service from the employees, whose  institutionalization  perception are  weak, will  not   be meaningful.  With  moving from  here, in  literature review  carried  out, any study  has not been  met about the  effect of    institutionalization   perception on emotional  labor  behavior. Hence, in this study,  an answer is searched for   the  main question “Does institutionalization  perception affect  emotional labor  behaviors? ” . In  the study,  it  aimed to   study  how institutionalization  perception has  an effect on    emotional labor  behaviors. The  main   hypothesis of     the study is: H1= Institutionalization perception of  employees affect  their emotional  labor   behaviors in positive   direction.  The study has a quality  of   empirical research.  In  the  study, survey   technique is  used  as data collecting instrument.  The  universe of  the  study consists  of   accommodation  businesses being  in  active. In the  study,  a valid    feedback   was obtained   from   420 workers. The  data obtained  in   this study will   be   analyzed by the  method   of simple  linear   regression methods. It  is   considered that   the  findings to be  obtained at the   end   of the study will  make  contribution to   eliminating the  deficiency in the  area and will  present useful opinions  toward the literature and application.    Keywords: Institutionalization , emotional  labor,  businesses